Do existing competitiveness models comprehensively assess the competitiveness context of the contemporary agribusiness sector? A systematic review - Muluken Ayalew Worku; Kenenisa Lemi Debela; Huub L.M. Mudde (Cogent Business & Management, 2024)
This review study intended to investigate how existing agribusiness competitiveness studies understood the competitiveness concept and the measurement employed. To address the aims, the study used a systematic review strategy, particularly using the PRISMA 2020 protocol. In this respect, clear inclusion and exclusion criteria were used to select 60 relevant articles from the total of 2,563 agribusiness competitiveness-focused articles obtained from various databases. The study also used content analysis to analyze the data that were gathered and descriptive research design to present the results descriptively. The finding shows that competitiveness concept is understood from marketing perspective or forward integration, particularly from export. Methodologically, the finding revealed that there is a shortage of studies conducted using explanatory design and inferential statistical analysis. RCA, Porter Diamond, and RTA models are the most accepted and applied models to investigate competitiveness in the existing studies but the first two in particular are not complete. Therefore, it is suggested that future studies focus on investigating agribusiness competitiveness using explanatory design and inferential statistical analysis. It is also recommended that NRCA, RTA, and the proposed competitiveness framework has to be used together to investigate agribusiness competitiveness comprehensively.
Keywords: 650; Agribusiness; competitiveness; measure; model; systematic review; PRISMA 2020 protocol